Review of BCL2 inhibitors for the treatment of Waldenström’s macroglobulinaemia and non-IgM lymphoplasmacytic lymphoma - Tomkins, Oliver (Frontiers in Oncology, 2024)
Lymphoplasmacytic lymphoma (LPL) is a relatively rare form of indolent B-cell non-Hodgkin’s lymphoma, termed Waldenström’s macroglobulinaemia (WM) in the presence of an IgM paraprotein. Although traditionally treated with combination chemoimmunotherapy, the management is evolving in the era of targeted molecular therapies including Bruton’s tyrosine kinase inhibitors (BTKi). However, intolerance and refractoriness to BTKi mean newer agents are required, and the prognosis of so-called quadruple-refractory patients is poor. BCL2 is an anti-apoptotic, pro-survival protein that promotes lymphoma cell survival. Inhibition of BCL2 using first-in-class agent venetoclax has already altered the treatment paradigm in other conditions, including chronic lymphocytic leukaemia (CLL). In-vivo inhibition of BCL2 has been shown to lead to apoptosis of LPL/WM cells. Five studies have published results on the use of BCL2 inhibitors in WM to date, including oblimersen sodium, venetoclax, and sonrotoclax. Fixed-duration venetoclax resulted in high response rates, but many patients relapsed following the completion of therapy. The combination of venetoclax with ibrutinib resulted in higher and relatively deep response rates, but unexpected deaths due to ventricular events mean this combination cannot be explored. Two pivotal trials are currently evaluating the use of fixed-duration venetoclax, either in combination with rituximab or pirtobrutinib, whereas another multi-arm study is studying the use of continuous sonrotoclax monotherapy for R/R WM or in fixed-duration combination with Zanubrutinib for treatment-naïve patients. The potential role of BCL2 inhibitors in WM/LPL remains under study, with many hopeful that they may provide an additional chemotherapy-free oral alternative for patients requiring treatment. In an indolent condition with existing effective treatment regimens, including CIT and cBTKi, cost-effectiveness and toxicity profile will be key, although an additional treatment modality for quadruple-refractory patients with limited treatment options is urgently required.